Modern Faith and Thought: trs. Geoffrey W. Bromley - Chethimattam, John B (Journal of Dharma, 1992)
Helmut Thielicke, Modern Faith & Thought, trs. Geoffrey W. Bromley. Grand Rapids, Mich. : Wm B. Eerdmans, 1990, pp.xix+ 582, $35.